Effects of essential oils from medicinal plants acclimated to Benin on in vitro ruminal fermentation of Andropogon gayanus grass - KOUAZOUNDE, BAMIKOLÉ JACQUES; JIN, Long; ASSOGBA, M. Fidèle; AYEDOUN, A. Marc; WANG, Yuxi; BEAUCHEMIN, A. Karen; McALLISTER, Tim A.; GBENOU, Djimon Joachim (My University, 2015)
Plants from West Africa commonly used in both human and veterinary medicine contain various secondary metabolites. However, their potential in mitigating ruminal CH4 production has not been explored. This study examined the eﬀects of EO from plants acclimated to Benin at four dosages (100, 200, 300 and 400 mg L−1), on in vitro rumen microbial fermentation and CH4 production using A. gayanus grass as a substrate. Compared to control, L. nobilis (300–400 mg L−1), C. aurantifolia (300 – 400 mg L−1) and O. gratissimum (200–400 mg L−1) decreased (P < 0.05) CH4 production (mL g−1 DM) by 8.1–11.8%, 11.9–17.8% and 7.9–30.6%, respectively. Relative to the control, reductions in CH4 (mL g−1 DM) of 11.4%, 13.5% and 14.2% were only observed at 400 mg L−1 for E. citriodora, O. basilicum and C. citratus, respectively. These EO lowered CH4 without reducing concentrations of total volatile fatty acids or causing a shift from acetate to propionate production. All EO (except M. piperita) reduced (P < 0.05) apparent DMD of A.gayanus. The current study demonstrated that EO from plants grown in Benin inhibited in vitro CH4 production mainly through a reduction in apparent DM digestibility.
Keywords: essential oil; in vitro; rumen; volatile fatty acids; digestibility; methane